STUDY HABITS INFLUENCE MOTIVATION TOWARDS LEARNING STUDENTS - Hasanah, Siti; Abdurakhman, Omon; Ichsan, Muhammad (Universitas Djuanda, 2016)
This study started from the premise that students 'learning habits affect the students' motivation. It is strengthened by seeing, reading and watching the existing reality in these days that students always given extra lessons beyond the limit when it will face a final exam. The purpose of this study was to test the students' learning habits on motivation to learn. Good study habits influence on motivation to learn at SDN Cisarua 03. The method used in this study is a simple linear regression. The data obtained in this study originated from the observation, documentation and questionnaire. The population in this research is class 5 A and 5 B amounting to 73 peoples, then of the 73 sampled by the number of 62 peoples. Sampling techniques in this study using random sampling with using Yamane formula taro. Instrument in this study consisted of 40 items of 20 questions for the variable study habits of student and 20 questions for the variable of learning motivation. Results from this study indicate that students' learning habits have influence with an average value of 38.20% through the regression equation Å¶ = 20.46 + 0,67X the remaining 61.80% is determined by other factors not included in the discussion on research this.